Do tetracyclines and erythromycin exert anti‐acne effects by inhibition of P450‐mediated degradation of retinoic acid?. Issue 4 (April 2014) - Hellmann‐Regen, Julian; Herzog, Irmelin; Fischer, Norina; Heuser, Isabella; Regen, Francesca
Abstract For decades, retinoic acid (RA) is known as the most potent therapeutic option in the therapy of acne and altered homeostasis of endogenous retinoids has been discussed in the context of acne pathogenesis. Besides retinoids, antibiotics such as tetracyclines or erythromycin are well established in acne pharmacotherapy. Accumulating evidence points towards common molecular pathways being targeted by both RA and anti‐acne antibiotics; however, a precise 'common denominator' connecting these chemically diverse anti‐acne agents has not yet been identified. Interestingly, tetracyclines are associated with the occurrence of pseudotumor cerebri, a rare neurological side effect otherwise associated with retinoid intoxication or RA exposure. This association at the clinical level suggests an interaction between tetracyclines and endogenous RA signalling. As erythromycin does not cross the blood brain barrier, CNS side effects are not to be expected, yet not precluding a possible local interaction of erythromycin with endogenous RA metabolism in the skin. We hypothesize tetracyclines and erythromycin to locally inhibit endogenous RA metabolism in the skin and thus mimic therapeutic action of RA. This readily testable hypothesis suggests inhibition of endogenous RA metabolism and amplification of endogenous RA signalling as a mechanism underlying the biochemical actions of antibiotics in acne therapy. Elucidation of such interactions may ultimately enhance our understanding of acne therapy and pathogenesis and may yield a sound, scientific basis for hypothesis‐driven development of novel therapeutic compounds.